Nepotism, incentives and the academic success of college students - Deniz Gevrek; Zahide Eylem Gevrek (Institute for the Study of Labor (IZA), 2008)
This study investigates the role of self-employed parents on their children's post-graduation plans and college success by using a unique data set from a private university in Turkey. We assembled data set by matching college students' administrative records with their responses to a survey we designed. Self-employed parents have a strong negative effect on college success even after accounting for possible ability bias, intergenerational human capital transfers and controlling for various individual characteristics. This suggests that the changing importance of self-employment can alter the amount and mix of human capital flows. The children of self-employed parents are also more likely to have entrepreneurial intent, and are less likely to plan to attend graduate school.
urn:nbn:de:101:1-2008101499
Keywords: J24; 330; Academic success; self-employment; post-graduation plans; Studierende; Bildungsabschluss; Familiensoziologie; Selbstständige; Unternehmer; Türkei